2000
DOI: 10.1073/pnas.050576397
|View full text |Cite
|
Sign up to set email alerts
|

Understanding hippocampal activity by using purposeful behavior: Place navigation induces place cell discharge in both task-relevant and task-irrelevant spatial reference frames

Abstract: Continuous rotation of an arena in a cue-rich room dissociates the stationary room-bound information from the rotating arenabound information. This disrupted spatial discharge in the majority of place cells from rats trained to collect randomly scattered food. In contrast, most place cell firing patterns recorded from rats trained to solve a navigation task on the rotating arena were preserved during the rotation. Spatial discharge was preserved in both the task-relevant stationary and the task-irrelevant rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 14 publications
2
41
0
Order By: Relevance
“…Although conclusive evidence has demonstrated that the hippocampal representations of space can be dissociated into separate frames of reference (Gothard et al, 1996a,b; Zinyuk et al, 2000; Knierim, 2002; Lee et al, 2004), these dissociations do not necessarily entail distinct mechanisms of the formation of spatial firing. Rivard et al (2004) showed evidence that there were at least two classes of place cells, one class that signals proximity to a barrier and another that signals location in an allocentric reference frame.…”
Section: Discussionmentioning
confidence: 99%
“…Although conclusive evidence has demonstrated that the hippocampal representations of space can be dissociated into separate frames of reference (Gothard et al, 1996a,b; Zinyuk et al, 2000; Knierim, 2002; Lee et al, 2004), these dissociations do not necessarily entail distinct mechanisms of the formation of spatial firing. Rivard et al (2004) showed evidence that there were at least two classes of place cells, one class that signals proximity to a barrier and another that signals location in an allocentric reference frame.…”
Section: Discussionmentioning
confidence: 99%
“…Epoch remapping may represent a mechanism by which the hippocampus is able to distinguish distinct events that occur in the same location, a critical component of episodic memory (Tulving, 1972). Observing three separate remapping patterns (no remapping, epoch remapping and task remapping) within the same population of neurons is an example of partial remapping, in which manipulations of the recording environment reveal subpopulations of place cells that are tied to separate reference frames (Gothard et al, 1996; Shapiro et al, 1997; Tanila et al, 1997; Skaggs and McNaugton, 1998; Zinyuk et al, 2000; Knierim, 2002; Anderson and Jeffery, 2003; Paz-Villagran et al, 2004). The partial remapping observed between the three behavioral epochs indicates that the epoch-unique place field representations occur in conjunction with a stable spatial code (place fields that did not remap between epochs), and task code (task remapping place fields).…”
Section: Discussionmentioning
confidence: 99%
“…We have used the active place avoidance paradigm to investigate cognitive information processing (Fenton et al, 1998; Zinyuk et al, 2000; Kelemen and Fenton, 2010; Kelemen and Fenton, 2013). Place information in hippocampal electrical activity toggles between the distinct stationary and rotating spatial frames during active place avoidance, indicating neural coordination (Kelemen and Fenton, 2010; Kelemen and Fenton, 2013).…”
Section: Methodsmentioning
confidence: 99%